Implementasi ISO 45001 dalam Meningkatkan Kinerja K3 di Berbagai Sektor Industri - Selvia Selvia; Firda Vinanda; Muhammad Raply; Abdurrozzaq Hasibuan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
. ISO 45001:2018 is an international standard for occupational health and safety (OHS) management systems designed to help organizations reduce the risk of workplace accidents and improve a safe and healthy work environment. This research uses a literature review method to explore the implementation of ISO 45001 in various industrial sectors, including construction, manufacturing, chemicals, and food processing. The study results show that the implementation of ISO 45001 has a significant positive impact on reducing workplace accidents, increasing productivity, and strengthening the safety culture. However, the implementation process also faces various challenges, such as limited resources, low commitment from top management, and organizational cultural barriers. Therefore, the success of the implementation requires a strategic, participatory, and sustainable approach.